Closing the birth registration gap for Every newborn facility birth: literature review and qualitative research - Masudah Paleker; Dorothy Boggs; Debra Jackson; Louise-Tina Day; Joy E. Lawn (Taylor & Francis Group, 2023)
Background Birth registration is vital to provide legal identity and access to essential services. Worldwide, approximately 166 million children under five years (just under 25%) are unregistered, yet >80% of all births occur in health facilities in most low- and middle-income countries (LMIC). Objectives This study, conducted in association with UNICEF, aims to review facility-based birth registration initiatives, and provide recommendations to close the gap between facility birth and birth registration rates in LMIC. Methods A literature review covering published and grey literature was conducted to identify facility-based initiatives to increase birth registration rates. Semi-structured in-depth interviews were conducted by audio-call with six key global stakeholders to identify additional initiatives, and further insights for barriers and enablers to close the gap. Results Academic databases and grey literature search yielded 21 studies meeting pre-specified inclusion criteria. Nine barriers preventing birth registration were identified and grouped into three themes: health system, governmental, and societal barriers. Facility-based birth registration initiatives resulted in an increase in birth registration rates. Importantly, health promotion within communities also increased demand for birth registration. In-depth interview respondents provided further detail and supported data found in literature review. Synthesis of the literature and stakeholder interviews noted enablers including inter-sectoral collaboration between health sector and civil registration ministries e.g., placing civil registration offices in health facilities or allowing medical doctors to act as registrars. Conclusion Facility-based birth registration initiatives can increase birth registration rates in LMIC. Initiatives need to address both supply and demand side of birth registration to improve facility-based birth registration rates. A multi-sectoral approach within governments, and alignment with multiple stakeholders is vital.